Detecting co-infections of Echinococcus multilocularis and Echinococcus canadensis in coyotes and red foxes in Alberta, Canada using real-time PCR. Issue 2 (August 2018) - Santa, Maria A.; Pastran, Sonya A.; Klein, Claudia; Duignan, Padraig; Ruckstuhl, Kathreen; Romig, Thomas; Massolo, Alessandro
Abstract: The continued monitoring of Echinococcus species in intermediate and definitive hosts is essential to understand the eco-epidemiology of these parasites, as well to assess their potential impact on public health. In Canada, co-infections of Echinococcus canadensis and Echinococcus multilocularis based on genetic characterization have been recently reported in wolves, but not yet in other possible hosts such as coyotes and foxes. In this study, we aimed to develop a quantitative real-time PCR assay to detect E. multilocularis and E. canadensis and estimate the occurrence of co-infections while inferring about the relative abundance of the two parasites within hosts. We tested DNA extracted from aliquots of Echinococcus spp. specimens collected from intestinal tracts of 24 coyote and 16 fox carcasses from Alberta, Canada. We found evidence of co-infections of E. multilocularis and E. canadensis in 11 out of 40 (27%) samples, with 8 out of 24 (33%) in coyote samples and 3 out of 16 (19%) in red fox samples. DNA concentrations were estimated in three samples with Cq values within the range of the standard curve for both parasites; two of them presented higher DNA concentrations of E. multilocularis than E. canadensis . The use of qPCR aided detection of co-infections when morphological discrimination was difficult and quantification of DNA for samples within the standard curve. This is the first molecularly confirmed record of E. canadensis in coyotes and the first evidence of co-infections of E. multilocularis and E. canadensis in coyotes and red foxes. Graphical abstract: Image 1 Highlights: We developed a quantitative real-time PCR assay to detect Echinococcus multilocularis and Echinococcus canadensis in definitive hosts. We report for the first time evidence of co-infections of E. multilocularis and E. canadensis in red foxes and coyotes. This is the first molecularly confirmed record of E. canadensis (G10) in coyotes in North America.